Determination of mycophenolic acid and its glucuronide conjugate in human plasma by capillary electrophoresis - (:unkn) unknown (VIEWEG, 2001)
In clinical transplantation mycophenolate mofetil (MMF) has become an attractive immunosuppressive agent. To quantify mycophenolic acid (MPA) and its main metabolite mycophenolic acid glucuronide (MPAG) from small plasma volumes, a capillary electrophoresis method has been developed, Separation of MMF and its metabolites MPA and MPAG was carried out in a 37 cm x 50 mum-l. D., fused silica capillary with an extended light path at the detection window (bubble-cell) and a TRIS buffer, pH 5.37 Detection was by UV at 214 nm. Sample preparation was by protein precipitation with acetonitrile and concentration of the supernatant. Naproxen was used as internal standard. Separation of MMF, MPA and MPAG was in less than 6 min. The method is reproducible and accurate, with lower limits of quantification of 0.5 mg L-1 for MPA and 2 mg L-1 for MPAG.
Keywords: capillary electrophoresis; mycophenolic acid; mycophenolic acid glucuronide; human plasma samples; PERFORMANCE LIQUID-CHROMATOGRAPHY; METABOLITE; MOFETIL; EMIT